Biodiesel production in a reactive distillation column catalyzed by heterogeneous potassium catalyst. (December 2017) - Pradana, Yano Surya; Hidayat, Arif; Prasetya, Agus; Budiman, Arief
Abstract: Biodiesel is a bio-based fuel synthesized from a renewable feedstocks, such as vegetable oils or animal fats. Conventionally, it is made through transesterificating oils where the process involves catalyst and alcohol to be reacted in batch reactor. The most common catalyst for biodiesel production is homogeneous liquid catalyst. These catalytic systems, however, are difficult on separating the final product and suffer from environmental problems because they are hazardous, caustic and hygroscopic. In order to eliminate the problems, we develop potassium loaded on activated carbon (K/AC) as heterogeneous solid catalyst. Heterogeneous solid catalyst is easily regenerated, leading to more secure, lower in cost, and more environmentally friendly. The purpose of this study is to demonstrate a process using catalytic reactive distillation column applied to biodiesel production from palm oil. Reactive distillation is the simultaneous process implementing reaction and separation process in a single column. This method presents several advantages such as increasing conversion, improving selectivity, reducing catalyst requirement, and avoidance azeotrope mixture. Reaction temperature (varied from 50 to 60 ° C) and methanol-palm oil molar ratio (varied from 4:1 to 8:1) were optimized to find the highest conversion in 4 hours. The higher reaction temperature accelerated the reaction rate, resulting higher conversion of oil into methyl ester. Meanwhile, the higher methanol-palm oil molar ratio affected slightly differences in reaction conversion. Reaction temperature should be limited to the boiling point of methanol to avoid the lower reaction rate causing by vaporization. Moreover, the methanol-palm oil molar ratio was also controlled by the availability of active site in the catalyst surface. Thus, the highest conversion of triglyceride, 0.8269, was obtained at temperature of 60 ° C and methanol-palm oil molar ratio of 6:1. It has proven that the continuous RD posses an enhanced performance on the biodiesel production, compared to batch reactor.